Scaffolds of Macroporous Tannin Spray With Human-Induced Pluripotent Stem Cells - Yang, Yongbo; Abdalla, Soliman (Frontiers in Bioengineering and Biotechnology, 2020)
Skeletal defects resulting from trauma and disease represent a major clinical problem worldwide exacerbated further by global population growth and an increasing number of elderly people. As treatment options are limited, bone tissue engineering opens the doors to start an infinite amount of tissue/bone biomaterials having excellent therapeutic potential for the management of clinical cases characterized by severe bone loss. Bone engineering relies on the use of compliant biomaterial scaffolds, osteocompetent cells, and biologically active agents. In fact, we are interested to use a new natural material, tannin. Among other materials, porous tannin spray-dried powder (PTSDPs) has been approved for human use. We use PTSDPs as reconstructive materials with low cost, biocompatibility, and potential ability to be replaced by bone in vivo. In this study, macro PTSDPs scaffolds with defined geometry, porosity, and mechanical properties are manufactured using a combination of casting technology and porogen leaching, by mixing PTSDPs and hydroxyapatite Ca10(PO4)6(OH)2 with polyethylene glycol macroparticles. Our results show that the scaffolds developed in this work support attachment, long-term viability, and osteogenic differentiation of human-induced pluripotent stem cell-derived mesenchymal progenitors. The combination of select macro porous PTSDPs scaffolds with patient-specific osteocompetent cells offers new opportunities to grow autologous bone grafts with enhanced clinical potential for complex skeletal reconstructions.